WEM-Platform: A real-time platform for full-body ergonomic assessment and feedback in manufacturing and logistics systems. (February 2022) - Battini, Daria; Berti, Nicola; Finco, Serena; Guidolin, Mattia; Reggiani, Monica; Tagliapietra, Luca
Highlights: WEM-Platform supports different inertial suits and activity tracker systems. Multi-objective ergonomic posture evaluation. Ergonomic risk indexes and feedback to workers are provided in real time. Post-processing data for additional analysis. Laboratory tests demonstrate the applicability of our ergonomic platform. Abstract: This article presents a new real-time full-body ergonomic platform: the Workforce Ergonomics and Management Platform (WEM-Platform). It provides ergonomic assessments in industrial and logistics environments based on motion capture using an inertial suit and an activity tracker. The platform also provides visual feedback to the workers involved in assembly, manufacturing, and picking operations. This innovative platform makes it possible to evaluate a set of ergonomic indexes (RULA, REBA, OWAS and PERA) and provide visual feedback in real-time to workers regarding posture and physical fatigue metrics. The graphical user interface (GUI) and the software were developed in house and support a variety of inertial suits, depth cameras, and activity tracker devices. The article discusses the WEM-Platform architecture, its state-of-the-art design, and crucially, its validation via rigorous laboratory testing.